The Role of Dividend Policy and Investment Decisions in Shaping Firm Value: Evidence from Indonesian Islamic Capital Market - Tajus Subqi; Maksum Maksum; Atep Hendang Waluya; Anna Zakiyah Hastriana; Rustam Rustam (Shirkah: Journal of Economics and Business, 2025)
While the previous studies have mentioned the effect of dividend policy and investment choice on the value of a firm, the effect of these variables on the value of a firm in the Islamic Capital Market of Indonesia has not been studied. Responding to this gap, the present study assesses the effect of dividend policy and investment choice on the value of a firm and examine how the dividend policy and investment choice affect the relationships of ownership structure, capital structure, profitability and corporation growth on the value of a firm. The study employed a quantitative method and collected data from 71 companies registered under the Indonesian Sharia Stock Index (ISSI) from 2016 to 2021. Using the software SmartPLS, the researchers did a Partial Least Squares (PLS) analysis to derive the required data. The results disclose that investment and dividend policies mediate the impact of capital structure on firm value but do not mediate the influence of ownership structure. Specifically, investment choice positively affects profitability, while dividend choice has a negative effect; furthermore, only dividend choice mediates corporate growth. Overall, both policies significantly determine firm value, particularly through their connection to capital structure and corporate growth. Managers and policymakers in the Indonesian Islamic capital market should strategically align dividend and investment policies with capital structure and growth considerations to enhance firm value in a Sharia-compliant context.